DESIGN AND IMPLEMENTATION OF INTERFACE SOFTWARE AND DIGITAL CONTROL PROGRAM IN STORAGE AND RETRIEVAL RACKING SYSTEM OF WAREHOUSES - Jogy Maratur Siburian, Arthur
In an automated storage and retrieval systems in warehouses, a link between the system and the user is needed and with himself (between software and hardware). For this reason, software system has been designed to handle the relationship between the database and the hardware interface and controller, the relationship between sensors and motor controllers with commands received from the user, and the relationship between the interface and the controller itself on a communication path between hardware and devices. soft. The implementation of this problem is in an MQTT-based IoT system for the network, FSM for the hardware information controller, C #-based GUI for the interface, MongoDB-based database for storage, and setup-loop control on the Arduino microcontroller with C ++ for digital controlling. The software implementation that has been done shows that the system is able to communicate with a latency of 3 ms and implements FSM which has a constant tolerance parameter of 3 cm and PID conversion parameters governed for execution if system position is at least 70% of the target. The design and implementation that has been done can be an alternative solution to the problems mentioned.